Zn(II) Production via a Pulsed Laser Ablation in Water: A Formation Mechanism of Zn and ZnO Nanoparticles#. (26th February 2015) - Lee, Seulki; Ahn, Ahreum; Choi, Myong Yong
<x xml:space="preserve">Abstract</x> <boxed-text content-type="graphic" id="bkcs10156-blkfxd-0001" position="anchor" orientation="portrait"> </boxed-text>